Molecular Characterization of Two Homozygous Factor VII Variants Associated with Intracranial Bleeding - Andersen, Elisabeth; Chollet, Maria Eugenia; Sletten, Marit; Stavik, Benedicte; Skarpen, Ellen; Backe, Paul Hoff; Thiede, Bernd; Glosli, Heidi; Henriksson, Carola Elisabeth; Iversen, Nina (Thrombosis and Haemostasis, 2021)
Clinical parameters have been extensively studied in factor (F) VII deficiency, but the knowledge of molecular mechanisms of this disease is scarce. We report on three probands with intracranial bleeds at an early age, one of which had concomitant high titer of FVII inhibitor. The aim of the present study was to identify the causative mutations and to elucidate the underlying molecular mechanisms. All nine F7 exons were sequenced in the probands and the closest family members. A homozygous deletion in exon 1, leading to a frame shift and generation of a premature stop codon (p.C10Pfs*16), was found in proband 1. Probands 2 and 3 (siblings) were homozygous for a missense mutation in exon 8, resulting in a glycine (G) to arginine (R) substitution at amino acid 240 (p.G240R). All probands had severely reduced FVII activity (FVII:C < 1 IU/dL). Treatment consisted of recombinant FVIIa and/or plasma concentrate, and proband 1 developed a FVII inhibitor shortly after initiation of treatment. The FVII variants were overexpressed in mammalian cell lines. No FVII protein was produced in cells expressing the p.C10Pfs*16 variant, and the inhibitor development in proband 1 was likely linked to the complete absence of circulating FVII. Structural analysis suggested that the G to R substitution in FVII found in probands 2 and 3 would destabilize the protein structure, and cell studies demonstrated a defective intracellular transport and increased endoplasmic reticulum stress. The molecular mechanism underlying the p.G240R variant could be reduced secretion caused by protein destabilization and misfolding.
Keywords: FVII deficiency; FVII inhibitor; intracranial bleeds; intracellular trafficking; endoplasmic reticulum stress